Palmar xanthomas - Anisha George; Bimal Kanish; Anuradha Bhatia (Wolters Kluwer Medknow Publications, 2014)
A middle-aged woman presented with a history of asymptomatic lesions over the palms, which were progressively increasing in number. Examination revealed 2-mm sized yellowish papules over the palmar surface of fingers. A clinical diagnosis of palmar xanthomas was made. Fasting lipids indicated elevations consistent with dysbetalipidemia, confirming the diagnosis. We recommend that the thyroid stimulating hormone level and serum electrophoresis should be done as part of the work-up for this rare condition.